The Reflective Practitioner in Professional Education - Lawrence-Wilkes, Linda; Ashmore, Lyn.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2014)
How important is it to be a reflective practitioner in education today? This book examines the reflective practitioner role and the scope of reflective activities in professional practice, revealing that critical thinking is rooted in a philosophical debate about notions of truth linked to differing learning approaches.
Keywords: Education; School management and organization; School administration; Educational sociology; Teaching; Educational psychology; Education -- Psychology; Education and sociology; Sociology, Educational; Industrial Psychology